Fluorosilicate glass with power-dependent up-conversion luminescence characteristic as well as preparation method and application thereof
By using fluorosilicate glass composed of SiO2-YbF3-KF-ErF3, a continuous and reversible color change from red to green was achieved by controlling the laser excitation power. This solves the problem of color control of light emission in a single material, and is suitable for anti-counterfeiting encryption, three-dimensional display and non-contact optical sensing. It has the advantages of high stability and low cost.
Patent Information
- Application Number
- CN202511843138.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-03-17
AI Technical Summary
Existing upconversion luminescent materials cannot achieve dynamic and reversible color modulation of emission in a single material, and traditional materials have problems such as insufficient stability or difficulty in preparation, which limit their application in real-time response devices.
Fluorosilicate glass composed of SiO2-YbF3-KF-ErF3 can achieve a continuous and reversible transition from red to green by controlling the laser excitation power. It is prepared by melt quenching, which is simple and low cost. The material has no phase separation inside and has low phonon energy and excellent physicochemical stability.
It achieves efficient and dynamic emission color control in a single material, is suitable for mass production, and can be applied to anti-counterfeiting encryption, 3D display and non-contact optical sensing. It also has a high laser damage threshold and other multifunctional characteristics.
Smart Images

Figure CN121672934A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optical glass material technology, specifically relating to a fluorosilicate glass with power-dependent upconversion luminescence characteristics, its preparation method, and its application. Background Technology
[0002] With the deep integration of photonics and information technology, the demand for high-performance optical functional materials is becoming increasingly urgent. Upconversion luminescent materials can convert low-energy near-infrared light into high-energy visible light through multiphoton absorption or energy transfer processes, showing broad application prospects in fields such as 3D display, optical storage, information encryption, bioimaging, and non-contact optical sensing. Achieving effective control over the color of upconversion emission is one of the core challenges in expanding its functional applications.
[0003] Currently, the mainstream strategies for controlling the color of upconversion emission mainly include the following approaches: First, by changing the inherent composition of the material, such as adjusting the type and concentration of doped rare earth ions or introducing co-doped ions, to finely control the energy transfer path; second, by designing complex core / shell structured nanocrystals and controlling the composition and thickness of each shell to regulate the cross-relaxation and energy transfer processes; and third, by using external stimuli such as temperature, pressure, excitation power, or wavelength. These stimuli can change the electron population of different energy levels of trivalent lanthanide ions, thereby adjusting the intensity ratio of different emission bands and achieving color control of the material's emission.
[0004] In existing technologies, the modulation of upconversion emission color mainly relies on changes in composition or complex structural design, making it impossible to achieve dynamic and reversible modulation of emission color in a single material. The synthesis process of core / shell nanocrystals is cumbersome, has poor reproducibility, and is costly, and the materials lack long-term stability, making it difficult to meet the needs of practical device applications. Composition-dependent modulation methods cannot achieve dynamic and reversible changes in emission color in a single material, limiting their application in real-time response devices. Furthermore, traditional upconversion material matrices, such as oxide glasses, while possessing good physicochemical stability, suffer from high phonon energies that severely restrict upconversion luminescence efficiency; while low-phonon-energy fluoride glasses or chalcogenide glasses face challenges such as difficult fabrication, poor mechanical properties, and low laser damage threshold.
[0005] Therefore, there is an urgent need in the field to develop a new type of upconversion luminescent material that can avoid complex nanosynthesis processes and achieve efficient, dynamic, and reversible full-color luminescence control in a single material system through simple and tunable external excitation conditions (such as excitation power), while also possessing excellent physicochemical stability and compatibility with preparation processes. Summary of the Invention
[0006] To address the aforementioned limitations of existing technologies, the present invention aims to provide a semiconductor laser-induced color-changing fluorosilicate glass, its preparation method, and its applications. By optimizing the composition and preparation process, the present invention designs and prepares a novel fluorosilicate glass system (SiO2-YbF3-KF-ErF3), which can achieve efficient power-dependent upconversion luminescence in a single glass material, realizing a continuous and reversible transition from red to green.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a fluorosilicate glass with power-dependent color modulation characteristics, wherein the fluorosilicate glass is prepared from SiO2, YbF3, KF and ErF3 in a molar ratio of (40-70):(15-30):(15-30):(0.2-1).
[0008] The term "fluorosilicate glass" refers to a new type of optical material that combines the stability of silicate glass with the low phonon energy advantage of fluoride glass, and is particularly suitable for rare earth ion doping to achieve efficient upconversion luminescence.
[0009] The term "single fluorosilicate glass material" refers to a single, homogeneous glassy substance formed by introducing specific fluorides (such as CaF2, AlF3, NaF, etc.) as modifiers, based on a silicate-based network framework. The material exhibits no significant phase separation (containing no independent fluoride crystals or other glassy phase impurities), and its composition and structure are uniform, distinguishing it from composite materials or multiphase materials consisting of "fluorosilicate glass + other materials."
[0010] There are currently no reports of efficient power-dependent upconversion luminescence and continuous reversible transition from red to green in a single fluorosilicate glass material.
[0011] The ratio of green light emission intensity to red light emission intensity of the fluorosilicate glass described in this invention, when excited by a 980 nm laser, can change linearly with the change of excitation power, and the ratio ranges from 0.21 to 2.44.
[0012] The power-dependent color modulation characteristic refers to the fact that under laser excitation at a wavelength of 980 nm, its upconversion emission color can change from red through orange and yellow to green in the range of excitation power from 48 mW to 1100 mW, achieving reversible color change.
[0013] This invention modulates the energy transfer mechanism inside the glass by using laser excitation power. At relatively low excitation power, the number of excited photons is small, and a large number of electrons are distributed in the ground state energy level. 2 F 7 / 2 , 4 I 15 / 2Therefore, cross-relaxation processes are more likely to occur, primarily filling the red emission energy levels, resulting in more significant red light emission than green light, and the upconversion emission color tends to be red. At high excitation power, a large number of excitation photons provide energy, causing a large number of electrons to be distributed in the excited state energy levels. 2 F 5 / 2 , 4 I 11 / 2 At this time, the cross-relaxation process is suppressed, and energy transfer between Er / Yb is more likely to occur. 4 I 11 / 2 + 2 F 5 / 2 → 4 F 7 / 2 + 2 F 7 / 2 This causes green light emission to dominate, and the upconversion emission color tends to be green. Ultimately, this results in a power-dependent multicolor upconversion emission phenomenon where red light dominates at low power and green light dominates at high power.
[0014] Compared with the prior art, the present invention has the following outstanding effects: (1) Simple preparation and low cost: The traditional melt quenching method is adopted, which does not require complex nano-synthesis or core-shell structure design, making it suitable for large-scale production.
[0015] (2) High stability: Fluorosilicate glass also has low phonon energy (approximately 500 cm⁻¹). -1 It exhibits excellent physicochemical stability and a high laser damage threshold.
[0016] (3) Dynamic color control: The color of light emission can be continuously and reversibly controlled by the excitation power in a single material without changing the composition or structure.
[0017] (4) Multifunctional applications: Its significant power-dependent multicolor upconversion luminescence can be used in fields such as anti-counterfeiting encryption, three-dimensional display, and non-contact optical sensing.
[0018] Preferably, the fluorosilicate glass has the following composition: 70SiO2-15YbF3-15KF-0.2ErF3.
[0019] In a second aspect, the present invention provides the application of the above-described fluorosilicate glass in (1) or (2) as follows: (1) Fabrication of optical functional devices; (2) Used for non-contact optical distance sensing and detection.
[0020] Preferably, the optical functional device is any one of a dynamic anti-counterfeiting mark, a power-dependent optical sensor, or a color-adjustable upconversion three-dimensional display element.
[0021] The non-contact optical distance sensing method includes the following steps: (1) An excitation beam of constant power is irradiated onto the fluorosilicate glass of claim 1 through a position-adjustable focusing optical system; (2) By changing the relative distance between the focusing optical system and the fluorosilicate glass, the area of the light spot irradiated on the glass surface and the laser power density are changed; (3) Collect and analyze the upconversion emission spectrum generated by the excitation of fluorosilicate glass. Based on the intensity ratio of the green light and red light emission peaks in the upconversion emission spectrum, and combined with the pre-calibrated mapping relationship curve between the G / R ratio and the relative distance, determine the current distance value.
[0022] The G / R ratio is the ratio of the emission intensity of green light at 521 nm to that of red light at 657 nm.
[0023] The curve obtained in this application shows a trend of first rising and then falling. The fitted curve to the right of the focal point is: R 2 =0.99313,FIR=0.26+1 / (0.085+0.008(x-6.25) 2 ).
[0024] This application proposes a novel ranging method based on power-dependent upconversion luminescence characteristics, which can be combined with camera imaging to achieve visualized ranging. A CCD camera captures the luminescence image of the sample, extracts its chromaticity coordinates, and compares them with a distance-chromaticity map established using spectral data to achieve quantitative distance estimation. Specifically, the process involves using a CCD to monitor the luminescence color of SYbK glass in real time, obtaining the CIE chromaticity coordinates under different lens displacements after image processing, and then measuring the distance by comparing the real-time acquired luminescence color chromaticity coordinates with the distance-chromaticity map.
[0025] In a third aspect, the present invention provides a method for preparing the above-mentioned fluorosilicate glass, comprising the following steps: (1) Weigh SiO2, YbF3, KF and ErF3 according to the proportion and grind them to obtain a mixture. Place the mixture in an air atmosphere at 1600-1700℃ and melt it for 20-30 minutes to obtain molten glass. (2) Quickly pour the molten glass into a metal mold that has been preheated to 200°C, and quench it for 10-20 seconds to form a glass solid; (3) Anneal the glass solid at 400-500℃ for 5-10 hours and cool it to room temperature to obtain fluorosilicate glass.
[0026] In a fourth aspect, the present invention provides a method for controlling the upconversion emission color of fluorosilicate glass. By using the aforementioned fluorosilicate glass as the luminescent medium and changing the excitation power of the incident 980 nm laser, the upconversion emission color output by the fluorosilicate glass can be controlled in real time, continuously, and reversibly.
[0027] The beneficial effects of this invention are: 1. This invention utilizes a fluorosilicate glass matrix (SiO2-YbF3-KF) and rare earth ions (Er) 3+ / Yb 3+ The unique design of the interaction allows for a continuous and reversible change in upconversion emission color from red, orange, yellow to green in a single-phase, non-core-shell bulk glass by simply changing the excitation power (48-1100 mW) of a 980 nm laser without contact.
[0028] 2. The melt quenching method used in this invention is simple, low-cost, and easy to scale up, overcoming the shortcomings of traditional core-shell nanocrystal synthesis processes that are complex and costly, and providing an ideal material platform for the development of novel multifunctional optical sensors and dynamic display devices. Attached Figure Description
[0029] Figure 1 Transmission spectra and photographs of different fluorosilicate glasses.
[0030] Figure 2 A photograph showing the change in luminescent color of a 70SiO2-15YbF3-15KF-0.2ErF3 fluorosilicate glass as a function of excitation power.
[0031] Figure 3 The upconversion spectrum and CIE chromaticity diagram of 70SiO2-15YbF3-15KF-0.2ErF3 fluorosilicate glass are shown.
[0032] Figure 4 The diagrams illustrate the application of distance measurement; (a) is a schematic diagram of the non-contact distance sensing experimental device based on the fluorosilicate glass of this invention, (b) shows the upconversion spectrum of the glass under different axial movement distances of the lens, and (c) is a graph showing the relationship between the experimentally measured G / R ratio and the axial movement distance of the lens. Detailed Implementation
[0033] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0034] The specific embodiments of the present invention will be described in further detail below with reference to examples. The following detailed descriptions are illustrative and intended to provide further explanation of this application, rather than limiting the scope of the invention.
[0035] Example 1: Sample preparation of glass with composition 40SiO2-30YbF3-30KF-0.4ErF3 (1) Weigh the raw materials according to the molar ratio of SiO2, YbF3, KF, and ErF3 of 40:30:30:0.4, and mix them evenly to obtain high-purity raw materials. Weigh a total of 20 grams of high-purity raw materials. Place the weighed raw materials in an agate mortar, grind and mix them thoroughly for 30 minutes, and then put them into a quartz crucible.
[0036] (2) The glass was melted and calcined at 1650℃ in air atmosphere for 25 minutes. The molten glass was then quickly poured onto a copper plate that had been preheated to 200℃. The glass was quenched for 15 seconds to form a glass solid. The resulting glass solid was then immediately transferred to an annealing furnace at 450℃ and annealed for 8 hours to eliminate internal stress. Finally, the glass was cooled to room temperature in the furnace to obtain a glass sample.
[0037] Example 2: Sample preparation of glass with composition 50SiO2-25YbF3-25KF-0.4ErF3 The molar ratio of SiO2, YbF3, KF, and ErF3 was adjusted to 50:25:25:0.4, and a glass sample was obtained according to the preparation method described in Example 1.
[0038] Example 3: Sample preparation of glass with composition 60SiO2-20YbF3-20KF-0.4ErF3 The molar ratio of SiO2, YbF3, KF, and ErF3 was adjusted to 60:20:20:0.4, and a glass sample was obtained according to the preparation method described in Example 1.
[0039] Example 4: Sample preparation of glass composition 70SiO2-15YbF3-15KF-0.4ErF3 The molar ratio of SiO2, YbF3, KF, and ErF3 was adjusted to 70:15:15:0.4, and a glass sample was obtained according to the preparation method described in Example 1.
[0040] Example 5: Sample preparation of glass with composition 70SiO2-15YbF3-15KF-0.2ErF3 The molar ratio of SiO2, YbF3, KF, and ErF3 was adjusted to 70:15:15:0.2, and a glass sample was obtained according to the preparation method described in Example 1.
[0041] Example 6: Sample preparation of glass composition 70SiO2-15YbF3-15KF-0.4ErF3 The molar ratio of SiO2, YbF3, KF, and ErF3 was adjusted to 70:15:15:0.4, and a glass sample was obtained according to the preparation method described in Example 1.
[0042] Example 7: Sample preparation of glass composition 70SiO2-15YbF3-15KF-0.6ErF3 The molar ratio of SiO2, YbF3, KF, and ErF3 was adjusted to 70:15:15:0.6, and a glass sample was obtained according to the preparation method described in Example 1.
[0043] Comparative Example 1: The raw materials were weighed according to a SiO2:KF molar ratio of 70:15, and a glass sample was obtained according to the preparation method described in Example 1. Testing revealed that the glass prepared in Comparative Example 1 could not achieve power-dependent upconversion luminescence.
[0044] Comparative Example 2 The raw materials were weighed according to a molar ratio of SiO2, KF, and YbF3 of 70:15:15, and a glass sample was obtained according to the preparation method described in Example 1. Testing revealed that the glass prepared in Comparative Example 2 could not achieve power-dependent upconversion luminescence.
[0045] Comparative Example 3: The raw materials were weighed according to a molar ratio of SiO2, KF, and ErF3 of 70:15:0.2, and a glass sample was obtained according to the preparation method described in Example 1. Testing revealed that the glass prepared in Comparative Example 3 could not achieve power-dependent upconversion luminescence.
[0046] Test Example: Performance Testing of Glass Samples The glass samples prepared in Examples 1-7 were cut into 1.5 cm wide cubes and polished to a thickness of 2 mm for transmittance spectroscopy and upconversion fluorescence spectroscopy analysis.
[0047] The transmission spectrum and photographs of the prepared fluorosilicate glass are as follows: Figure 1 The glass exhibits excellent optical transmittance in the visible light region (>80%), with six distinct absorption peaks located at 378, 521, 651, 978, and 1532 nm. The absorption peaks at 378, 521, 651, and 1532 nm correspond to Er... 3+ From the ground state 4 I 15 / 2 energy level to 4 G 11 / 2 , 2 H 11 / 2 , 4 F9 / 2 and 4 I 13 / 2 Absorption in the excited state.
[0048] A glass with the composition 70SiO2-15YbF3-15KF-0.2ErF3 was selected from the fluorosilicate glass series for testing. The fluorosilicate glass exhibits upconversion emission color control through excitation power. Under 980nm laser excitation, a continuous and reversible color transition from red, orange, and yellow to green can be achieved simply by changing the excitation power. A physical image of the luminescent glass is shown below. Figure 2 Fluorescence spectroscopy was performed using an Edinburgh steady-state transient fluorescence spectrometer (FLS100), and the results are as follows: Figure 3 As shown, the upconversion luminescence of 70SiO2-15YbF3-15KF-0.2ErF3 glass gradually increases with increasing excitation power, but exhibits power-dependent multicolor upconversion luminescence characteristics. At low power, red light dominates, while at high power, green light dominates. The corresponding CIE diagram also shows that the color-changing phenomenon of fluorosilicate glass can span both the red and green color regions.
[0049] Application example: Non-contact high-precision distance sensing based on the power-dependent luminescence properties of fluorosilicate glass To demonstrate the application potential of the fluorosilicate glass described in this invention in the field of optical sensing, a non-contact distance sensing demonstration system was constructed. Its core principle lies in utilizing the focusing and diverging effects of a lens on a laser spot to alter the power density irradiated onto the glass sample surface, thereby exciting it to produce different upconversion emission colors (G / R ratios). By establishing a mapping relationship between the color (G / R ratio) and the lens-sample distance, distance measurement is achieved.
[0050] (1) Experimental setup and principle: A schematic diagram of the experimental setup is shown below. Figure 4 As shown in (a), a constant-power 980 nm laser beam passes sequentially through a beam expander and collimator system, a movable focusing lens whose axial position is precisely controlled by a stepper motor, and a semi-transparent mirror. One beam is used by a spot analyzer to monitor the spot area illuminating the sample surface in real time, while the other beam excites the upconversion fluorescence generated by the sample and is collected by a fluorescence spectrometer. When the total output power of the fixed laser remains constant, the laser power density on the sample surface is inversely proportional to the spot area, which is determined by the focal length of the focusing lens and the distance between the lens and the sample. Therefore, by changing the distance by axially moving the lens, the power density at the sample can be continuously adjusted.
[0051] (2) Experimental results and phenomena: The glass prepared in Example 1, with a composition of 70SiO2-15YbF3-15KF-0.2ErF3 (labeled SYbK), was selected as the sensing probe. Figure 4 As shown in (b), as the lens gradually approaches the glass sample, the spot area first shrinks and then increases, resulting in a power density that first increases and then decreases. Correspondingly, under 980 nm laser excitation, the upconversion emission color of the glass undergoes a continuous and reversible change from red → orange → yellow → green, and then in reverse from green → yellow → orange → red. This intuitively demonstrates the dependence of emission color on power density.
[0052] (3) Sensor calibration and performance: Color was characterized by the ratio of green light emission intensity at 521 nm to red light emission intensity at 657 nm (G / R ratio) through quantitative analysis using a spectrometer. The G / R ratios at different lens positions were recorded, and a curve showing the relationship between the G / R ratio and the axial movement distance of the lens was plotted. Figure 4 As shown in (c), the curve exhibits a trend of first rising and then falling, with the highest sensitivity near the focal point. Experimental results demonstrate that the system can achieve displacement resolution on the order of 100 micrometers (µm), showcasing the application potential of the material of this invention in high-precision, non-contact optical distance sensing.
[0053] The above description is merely a preferred embodiment of this application and is not intended to limit the application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications made within the spirit and principles of this application are not permitted. Equivalent substitutions and improvements should all be included within the scope of protection of this application.
Claims
1. A fluorosilicate glass having power-dependent color regulation characteristics, characterized in that, The fluorosilicate glass is prepared from SiO2, YbF3, KF and ErF3 in a molar ratio of (40-70):(15-30):(15-30):(0.2-1).
2. The fluorosilicate glass of claim 1, wherein The ratio of the green light emission intensity to the red light emission intensity of the upconversion luminescence of the fluorosilicate glass under 980 nm laser excitation changes linearly with the change of the excitation power, and the ratio change range covers 0.21 to 2.
44.
3. The fluorosilicate glass of claim 1, wherein The power-dependent color control characteristic refers to that under the excitation of a laser with a wavelength of 980 nm, the color of the upconversion luminescence can change from red to orange, yellow and then to green in sequence within the excitation power range of 48 mW to 1100 mW, realizing reversible conversion.
4. The fluorosilicate glass of claim 1, wherein The fluorosilicate glass has a composition of 70SiO2-15YbF3-15KF-0.2ErF3.
5. The fluorosilicate glass of claim 1 is applied in (1) or (2) as follows: (1) preparation of optical functional devices; (2) for non-contact optical distance sensing.
6. Use according to claim 5, characterized in that, The optical functional device is any one of a dynamic anti-counterfeiting mark, a power-dependent optical sensor or a tunable color upconversion three-dimensional display element.
7. Use according to claim 5, characterized in that, The non-contact optical distance sensing method comprises the following steps: (1) irradiating a constant-power excitation light beam onto the fluorosilicate glass of claim 1 through a position-adjustable focusing optical system; (2) changing the relative distance between the focusing optical system and the fluorosilicate glass to change the spot area and laser power density on the glass surface; (3) collecting and analyzing the upconversion luminescence spectrum generated by the excitation of the fluorosilicate glass, determining the current distance value according to the intensity ratio of the green light emission peak to the red light emission peak in the upconversion luminescence spectrum, and combining the pre-calibrated mapping relationship curve of the G / R ratio and the relative distance.
8. Use according to claim 7, characterized in that, The G / R ratio is the intensity ratio of the green light at 521 nm to the red light at 657 nm.
9. A method of making the fluoro silicate glass of claim 1, characterized in that, The method comprises the following steps: (1) proportionally weighing SiO2, YbF3, KF and ErF3, grinding to obtain a mixture, and melting the mixture in an air atmosphere at 1600-1700℃ for 20-30 minutes to obtain a molten glass liquid; (2) rapidly pouring the molten glass liquid onto a metal mold preheated to 200℃, and quenching for 10-20 seconds to form a glass solid; (3) annealing the glass solid at 400-500℃ for 5-10 hours, and cooling to room temperature to obtain the fluorosilicate glass.
10. A method of tuning the color of upconversion luminescence from a fluorosilicate glass, characterized in that, By using the fluorosilicate glass of claim 1 as a luminescent medium, the excitation power of the incident 980 nm laser is changed to real-time, continuous and reversible control the color of the upconversion luminescence output by the fluorosilicate glass.